STRUCTURE OF IXODES TICK COMMUNITIES AT THE CONTINENTAL PART OF SOUTH PRIMORYE TERRITORY AND RUSSIAN ISLAND - A. Ya. Nikitin; T. V. Zvereva; N. S. Gordeiko; E. A. Borisenko; Yu. A. Verzhutskaya; T. A. Kameneva (Acta Biomedica Scientifica, 2012)
In April-June 2012 a collection and analysis of structure of Ixodes tick communities was performed in various biotopes at the Primorye Territory. Five tick species (Ixodes persulcatus Schulze, 1930, I. pavlovskyi Pomerantzev, 1946, Haemaphysalis concinna Koch, 1844, H. japonica douglasi Nuttall et Warburton 1915, Dermacentor silvarum Olenev, 1932) were revealed. It was shown that I. pavlovskyi was rare at the continental part of the Primorye Territory, but it often happened at the Russian island. On the Continent H. japonica douglasi prevailed over H. concinna in total collections. Correlation of these species at the Russian island was reversed. Distinctions in the structure of Ixodes tick communities, formed due to specificity of ecological conditions and. long enough isolation of the parasites' fauna at the island, could affect the ratio and. features of the causative agents of the human infectious diseases for which the carrier organism serves as the first environment.